Laser-processed Nanostructures of Metallic Substrates for Surface- Enhanced Raman Spectroscopy - Bai, Shi; Zhou, Weiping; Tao, Chen; D. Oakes, Ken; Hu, Anming (Current Nanoscience, 2014)
Surface-enhanced Raman spectroscopy (SERS) is rapidly emerging as a powerful analytical tool for trace analysis of metallic substrates. While innovative numerical applications of SERS have been developed, it is still a challenge to fabricate cost-effective and reproducible metallic substrates for SERS probes. Laser processing, especially using ultrafast pulsed laser, can address this issue owing to their high quality processing. Herein, we investigate critical technical requirements and the latest advancements in laser-processing substrates for SERS, while highlighting several diverse applications. In light of its powerful enhancement of Raman scattering, SERS will remain an exciting research area for highly sensitive, resolved analysis into the foreseeable future.
Keywords: Raman scattering